2002
DOI: 10.1542/peds.110.6.1125
|View full text |Cite
|
Sign up to set email alerts
|

Intersite Differences in Weight Growth Velocity of Extremely Premature Infants

Abstract: Variation in nutrition explained much of the difference in growth among the NICUs studied. Mean intake of calories and protein failed to meet recommended levels, and the average growth in only 1 NICU approximated intrauterine growth standards. Increasing nutritional intake into the recommended ranges, in particular of protein, may increase growth of extremely premature infants up to or above intrauterine rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 31 publications
8
99
2
3
Order By: Relevance
“…Furthermore, our observation that the protein intake of 3.5 g kg À1 per day in our P/E group, which was associated with improved postnatal growth, is consistent with the published literature. [14][15][16]25,26 Our study was limited by the small number of infants enrolled, but, as significant differences in growth are seen despite the limited number of infants, we believe that this observation is clinically significant. Nevertheless, it is possible with a larger sample size that growth rates would not have differed between groups or that days on steroids would be significantly different between groups.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, our observation that the protein intake of 3.5 g kg À1 per day in our P/E group, which was associated with improved postnatal growth, is consistent with the published literature. [14][15][16]25,26 Our study was limited by the small number of infants enrolled, but, as significant differences in growth are seen despite the limited number of infants, we believe that this observation is clinically significant. Nevertheless, it is possible with a larger sample size that growth rates would not have differed between groups or that days on steroids would be significantly different between groups.…”
Section: Discussionmentioning
confidence: 94%
“…18 Our findings of the importance of the type of calories supplied for in-hospital preterm growth have been emphasized by other investigators. [14][15][16][24][25][26][27][28][29][30] In 1998, Carlson and Zeigler 24 published a longitudinal study of 51 preterm infants and their protein intake, energy intake and subsequent growth. Regression analysis suggested that protein intake related positively to growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When growth of preterm infants lags behind expected growth (that is, growth like the fetus), it is almost always protein that is limiting growth. [21][22][23] Energy, on the other hand, provided that intakes are at least 90 to 100 kcal kg À1 per day, is seldom limiting for growth. Therefore, the inadequate levels of actual protein intakes observed in the present study offer an explanation of why preterm infants fail to grow adequately in spite of receiving adequate energy intakes.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Early parenteral amino-acid administration improves postnatal growth and decreases extrauterine growth restriction (EUGR). [6][7][8] Matching the catabolic rate of protein prevents negative protein balance. Studies have shown that achieving close to 3 g kg À1 per day of protein shortly after birth decreases postnatal weight loss, leads to an earlier return to birth weight and improves weight at 36 weeks postmenstrual age.…”
Section: Introductionmentioning
confidence: 99%